(untitled) (Materiali di Estetica. Terza serie, 2017)
Fassbinder’s In a Year of Thirteen Moons is not only a reflection, inspired by Schopenhauer’s philosophy, about suicide and its legacy, but it’s also a mise en scène of the short circuit of the dialectic struggle between the opposites, expressed by the transsexual main character of the movie Elvira, who shows in parallel, with her irreprehensible transitional body from a sex to another, the radical impossibility of social integration undermining the organization of the aedipical family, upon which bourgeois hierarchy of patriarchal society is based. Her diversity is not related to the capitalistic society’s dual logic and to its Manichaean dialectic of values, exposed by Fassbinder’s melodramas, which are similar to Verdi’s operas, loved by him.